Research Vessel POSEIDON - Klas Lackschewitz; Maike Heinitz (Journal of large-scale research facilities JLSRF, 2015)
The research vessel POSEIDON, operated by GEOMAR Kiel, is an important research platform for the marine science community. The knowledge gained from ocean expeditions contributes to a better understanding of the biological, physical, geological and chemical processes in the ocean.